2019
DOI: 10.1063/1.5080171
|View full text |Cite
|
Sign up to set email alerts
|

Weak surface electron-phonon coupling in the topological insulator Bi2Se3 nanoparticles revealed by electron spin resonance

Abstract: Hydrogen-doping of Bi2Se3 nanoparticles has provided a rare opportunity to study the surface state of a topological insulator by means of electron spin resonance (ESR) and static magnetization measurements. As a result, a weak surface electron-phonon coupling in the topological insulator Bi2Se3 nanoparticles was revealed by ESR signals that were attributed to the surface conduction electrons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 46 publications
2
11
0
Order By: Relevance
“…No ESR signal was detected in the pristine Al 2 O 3 , CoO, and Fe 2 O 3 nanoparticles. The ESR signals originate from the surface conduction electrons of the Bi 2 Se 3 nanoparticles, as reported in our previous works 16,23. Figure4(a,b) show the ESR intensity and linewidth obtained from the Dysonian fits as a function of the molar ratio of the ordinary insulator to Bi 2 Se 3 24.…”
supporting
confidence: 66%
See 1 more Smart Citation
“…No ESR signal was detected in the pristine Al 2 O 3 , CoO, and Fe 2 O 3 nanoparticles. The ESR signals originate from the surface conduction electrons of the Bi 2 Se 3 nanoparticles, as reported in our previous works 16,23. Figure4(a,b) show the ESR intensity and linewidth obtained from the Dysonian fits as a function of the molar ratio of the ordinary insulator to Bi 2 Se 3 24.…”
supporting
confidence: 66%
“…The ESR signals originate from the surface conduction electrons of the Bi 2 Se 3 nanoparticles, as reported in our previous works. 16,23 Figure 4(a,b) show the ESR intensity and linewidth obtained from the Dysonian fits as a function of the molar ratio of the ordinary insulator to Bi 2 Se 3 . 24 In the Bi 2 Se 3 nanoparticles mixed with the nonmagnetic Al 2 O 3 nanoparticles (S1), the ESR intensity increases with the molar ratio of Al 2 O 3 , and the ESR linewidth is nearly independent of the molar ratio.…”
Section: Resultsmentioning
confidence: 99%
“…Positron annihilation spectroscopy can provide unique information in the characterization of vacancies and vacancies attached defects ( e . g ., dislocations, misfit defects, and interfaces). , In the case of Bi 2 Te 3 -based alloys doped with transition metals or rare-earth elements, electron spin resonance can explore localized spins and reveal the intensity of electron–phonon coupling, which is important for evaluating TE properties. , The local structure information can be observed via extended X-ray-absorption fine-structure spectra, such as the interatomic distance, the locations of impurity sites, the locational fluctuations around impurity atoms, and the lattice distortions. In turn, the crystallographic structure in detail can provide basic information for first-principles calculations to quantify research on TE properties.…”
Section: Summary Challenges and Perspectivesmentioning
confidence: 99%
“…3,13,14 In previous studies, we showed that mixing topological insulator nanoparticles with ordinary insulator nanoparticles could increase the surface-to-volume ratio to identify the metallic surface states. 15,16 The mixing of topological insulator nanoparticles with ferromagnetic insulator nanoparticles can be expected to result in a magnetic proximity effect. 17 Room temperature ferromagnetism has been reported in various types of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%